AI-Based Defect Identification in FDM-Printed Biodegradable Polymer Composites Through Multimodal Characterization - Subramani, Raja; Sekhar, K.Ch.; Dwivedi, Jaiprakash Narain; Venkateswarlu, V.; Maddike, Ramamohana Reddy; Kumar, Avvaru Praveen (Journal of Composites and Biodegradable Polymers, 2025)
The growing demand for biodegradable polymer composites in sustainable manufacturing requires robust quality-assessment frameworks that ensure structural reliability and functional performance. However, FDM-based additive manufacturing of such materials often introduces processing-induced defects that compromise mechanical integrity. Conventional visual inspection remains subjective and limited, creating a need for advanced, automated defect-identification strategies. This study addresses this challenge by integrating artificial intelligence with multimodal characterization to establish a reliable defect-detection pipeline for FDM-printed biodegradable polymer composites. Biodegradable PLA-based composites reinforced with microscale and nanoscale fillers were fabricated under controlled FDM conditions, followed by systematic defect mapping through optical imaging, SEM, and surface profilometry. A convolutional neural-network classifier was trained using 2,500 labelled images, incorporating multimodal inputs to identify four major defects: voids, layer gaps, surface roughness irregularities, and under-extrusion patterns. The optimized AI model achieved an overall classification accuracy of 96.4%, precision of 94.8%, recall of 95.3%, and an F1-score of 95.0%, outperforming traditional threshold-based and handcrafted-feature methods. Multimodal correlation analysis further revealed that defects predicted with high probability aligned strongly with SEM-verified structural anomalies (R² = 0.93) and surface-roughness deviations (up to 18% variation). These results demonstrate that AI-assisted evaluation offers a reliable, scalable, and non-destructive pathway to improve defect quantification in biodegradable polymer composites. The proposed framework enhances process monitoring, reduces inspection subjectivity, and provides new insights into structure–processing–defect interrelationships in FDM-printed sustainable composites.